2017
DOI: 10.1002/cncr.31165
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrence, prognosis, and follow‐up for Danish women with cervical cancer in 2005‐2013: A national cohort study

Abstract: This study has identified a group of women at FIGO stage 1A1 in no need of specialized, hospital-based follow-up. Many of the recurrences at FIGO stage 1B1 are asymptomatic, and this may show a need for follow-up in this group. Further prospective investigation is needed. Cancer 2018;124:943-51. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 26 publications
4
39
2
Order By: Relevance
“…► Cytology and human papillomavirus (HPV) detection are recommended at 12 and 24 months, and then yearly after fertilitysparing surgery. [35][36][37] ► Imaging studies are not routinely recommended but are indicated in women with symptoms. 20 High Risk Up to 30% of patients with locally advanced cervical cancers will relapse after complete response to primary treatment.…”
Section: Telemedicine Risk-stratified Surveillance By Disease Site Cementioning
confidence: 99%
“…► Cytology and human papillomavirus (HPV) detection are recommended at 12 and 24 months, and then yearly after fertilitysparing surgery. [35][36][37] ► Imaging studies are not routinely recommended but are indicated in women with symptoms. 20 High Risk Up to 30% of patients with locally advanced cervical cancers will relapse after complete response to primary treatment.…”
Section: Telemedicine Risk-stratified Surveillance By Disease Site Cementioning
confidence: 99%
“…However only 4-5% will have pelvic recurrences and only 1-2% can be salvaged 28,31,32 , although this has increased slightly with cyberknife and other techniques. In a large Danish national cohort study of 1523 patients with low-risk cervical cancer, of those with recurrent disease, 67.5% experienced a symptomatic recurrence 30 Other studies have shown similar rates of symptomatic recurrent cervical cancer 24 . Therefore, as the majority present with symptoms, PIFU appears to be reasonable for low-risk patients.…”
Section: Endometrial Cancermentioning
confidence: 95%
“…However, vaginal vault cytology should not be performed following treatment for FIGO stage ≥IA2 as it does not add significantly to the detection of recurrent disease 25, [27][28] . These patients have a 5-year risk of recurrence of 5.8-8% 27,[29][30][31] . However only 4-5% will have pelvic recurrences and only 1-2% can be salvaged 28,31,32 , although this has increased slightly with cyberknife and other techniques.…”
Section: Endometrial Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Despite substantial development in understanding the molecular mechanisms and treatment for CC in recent years, the overall 5-year survival rates are not very encouraging [5,6]. The most com-DOI: 10.1159/000487595 mon therapeutic methods for CC are surgery, radiotherapy, and chemotherapy [7][8][9]. However, due to a lack of effective biomarker screening and restricted diagnosis technology, more sensitive and specific markers for diagnosis at early stage and more efficient and safer treatments are urgently needed.…”
Section: Introductionmentioning
confidence: 99%